The New England States and Their Economic Future: Some Implications of a Changing Industrial Environment - Meyer, John R.; Leone, Robert A. (American Economic Review, 1978)
Perhaps the most striking feature of the New England economy is that it is different-not only from the rest of the nation, but from the rest of the northeastern United States as well. New England's main departure from the national norm is, of course, relatively slow growth; it is conventional to describe New England as -economically, industrially, and maybe even demographically. This maturity manifests itself in many ways. While aggregate personal income in the United States expanded at an average annual rate of 4. 1 percent between 1960 and 1975, New England expanded at a rate of 3.6 percent per annum. Further, total manufacturing employment in Massachusetts and Rhode Island is only slightly higher today than in 1914. In the recent recovery from recession, New England lagged well behind the rest of the United States in expansion of total employment but nevertheless recorded some of the sharpest declines in unemployment rates so that New England unemployment is now near the national average even though it was much higher at the depth of the 1975 recession. The secret, of course, to New England's relatively rapid unemployment decline is slow workforce growth, as expected in a mature economy. New England's differences from the rest of the Northeast are perhaps less obvious and certainly less well known. It is fashionable today to speak in very broad terms of vs. sunbelt and to suggest that public policy should modulate differences in growth among the different sections of the country. The reality, though, is that aggregate figures for large regions of the country hide a good deal of internal diversity. Thus, New England not only seems to be doing better than conventional frostbelt wisdom would suggest, but its immediate prospects also appear more favorable than those of the mid-Atlantic states and probably much of the Midwest as well (see Benjamin Stevens and Glinnis Trainer). Even in the recent past, as between 1960 and 1976, when New England's aggregate personal income was growing 3.6 percent per year, the states of New York, New Jersey, Pennsylvania, Maryland, and Delaware had a combined average annual compound growth rate of only 3.3 percent. Similarly, a shift-share analysis has indicated that the entire Northeast (by virtue of a favorable industry mix) should have been in a position to gain in share of U.S. jobs throughout the 1960's. The New England states (except for extreme northern Maine) have indeed done as expected. Large areas of the remaining Northeast, however, have experienced significant competitive shifts or losses (see Richard Olsen). To a considerable extent, in fact, any New England success in recent years may have been at the expense of its immediate neighbors. New England production costs perhaps have not been as low as in much of the Southeast in recent years, but they apparently have been competitive with the Middle Atlantic, and especially New York City. In fact, total manufacturing costs in several industries (for example, ordnance, primary metals, fabricated metals, nonelectrical machinery, transportation equipment, paper and printing) have been lower recently in Massachusetts (probably the highest cost New England Harvard University. The Economic Development Administration of the U.S. Department of Commerce and the 1907 Foundation provided financial support for this research.